ANALISIS TINGKAT KESEHATAN PT. BANK TABUNGAN NEGARA DENGAN METODE RGEC - Iik Sufrizal Chaniago; Puji Hadiyati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2021)
This study aims to determine the analysis of the soundness of the bank using the RGEC (Risk Profile, Good Corporate Governance, Earnings and Capital) method at PT. State Savings Bank. This study uses secondary data at PT. BTN for a nine-year period from 2012 to 2020. The analytical technique used is the analytical technique using the RGEC (Risk profile, Good Corporate Governance, Earning, and Capital) method. This study proves that the soundness of the bank with the RGEC method at PT. BTN 2012-2020 in terms of risk profile with the NPL proxy having a Composite Rating (PK) 2 or Healthy and with the LDR proxy having a PK 4 or Less Healthy. From the aspect of good corporate governance, the self-assessment has a PK of 2 or Good. In terms of earnings, the ROA proxy has a PK of 2 or Healthy and the BOPO proxy has a PK of 3 or Fairly Healthy. Judging from the capital aspect, the CAR proxy has a PK of 1 or Very Healthy.